2007
DOI: 10.1302/0301-620x.89b1.18011
|View full text |Cite
|
Sign up to set email alerts
|

The femoral head/neck offset and hip resurfacing

Abstract: Because the femoral head/neck junction is preserved in hip resurfacing, patients may be at greater risk of impingement, leading to abnormal wear patterns and pain. We assessed femoral head/neck offset in 63 hips undergoing metal-on-metal hip resurfacing and in 56 hips presenting with non-arthritic pain secondary to femoroacetabular impingement. Most hips undergoing resurfacing (57%; 36) had an offset ratio Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 48 publications
1
46
0
1
Order By: Relevance
“…Therefore, we used these measures to determine the learning curves. Other radiographic measures suggested as possibly important in successful resurfacing include acetabular version and the femoral stem position on lateral imaging (impingement, retroversion, and touching the femoral cortex) [10,15,24,33,38,39,42,47]. The data supporting the importance of these measures is less compelling, so in this study, they were termed ''secondary goals.''…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, we used these measures to determine the learning curves. Other radiographic measures suggested as possibly important in successful resurfacing include acetabular version and the femoral stem position on lateral imaging (impingement, retroversion, and touching the femoral cortex) [10,15,24,33,38,39,42,47]. The data supporting the importance of these measures is less compelling, so in this study, they were termed ''secondary goals.''…”
Section: Discussionmentioning
confidence: 95%
“…One of us (RBB) reviewed these radiographs for periprosthetic lucency or loosening according to the systems of DeLee and Charnley [7] for acetabular lucency and Gruen et al [9] for femoral periprosthetic lucency, uncovered anterior components that may lead to iliopsoas tendonitis [25] or evidence of impingement (insufficient head neck offset ratio) of the residual femoral neck after total hip resurfacing [2,18]. It should be noted that substantial interobserver variability exists in assessment of periprosthetic lucency.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study reported approximately 57% of hips undergoing resurfacing had decreased head-neck offset (B 0.15) on preoperative radiographs [22]. In comparison to total hip arthroplasty, hip resurfacing preserves the femoral headneck junction.…”
Section: Femoroacetabular Impingementmentioning
confidence: 99%
“…Therefore, failure to restore adequate headneck offset may lead to femoroacetabular impingement and pain postoperatively. Hip resurfacing patients with impingement may experience abnormal wear patterns and pain, especially with malpositioned implants [22]. Adequate removal of femoral neck osteophytes is important to restore head-neck offset, prior to femoral head preparation, to ensure accurate component sizing and positioning, which will minimize the potential for postoperative impingement [24].…”
Section: Femoroacetabular Impingementmentioning
confidence: 99%
See 1 more Smart Citation